Mengungkap Persepsi Guru Terhadap Toleransi Sosial di Kalangan Siswa: Studi Kasus di Sekolah Dasar - Amanatullah, F Nurul Jihan Rizky; Herlina, Herlina; Firmansyah, Arif; Muchdar, Muchdar (Primera Educatia Mandalika: Elementary Education Journal, 2024)
This research is descriptive qualitative research. The problem in this research is how teachers perceive social tolerance among students: Case study in elementary schools. The data collection techniques are observation, interviews and document study. After the data is collected, the data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this research show that, Revealing teachers' perceptions of social tolerance among students: Case study in elementary schools. has been implemented and is in the good category, proven by the teacher's notes and the results of observations. Teachers have developed an attitude of tolerance in socializing so that students can differentiate how to socialize and understand how to work together with other friends who have different views.